Malignant [videorecording (DVD)] - Wan, James, 1977-; Wallis, Annabelle, 1984-; Hasson, Maddie, 1995-; Young, George, 1980- (Warner Home Video, 2021)
Madison is paralyzed by shocking visions of grisly murders, and her torment worsens as she discovers that these waking dreams are in fact terrifying realities.